Glass laminate and manufacturing method of glass laminate

JP2025001987APending Publication Date: 2025-01-09NITTO DENKO CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023101835
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-21
Publication Date
2025-01-09

AI Technical Summary

Benefits of technology

【0007】 高温環境下でのガラス積層体の優れた耐屈曲性を確保できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025001987000001_ABST
    Figure 2025001987000001_ABST
Patent Text Reader

Abstract

To secure excellent flex resistance of a glass laminate under a high temperature environment.SOLUTION: A glass laminate comprises a glass film having a first principal plane and a second principal plane, and a resin film adhered at least to the first principal plane. When a measurement sample of the rectangular glass laminate whose product of the long side and the short side is 8000 mm2 or more, and whose ratio of the long side / the short side is 2.5 or less is heated at 100°C for 30 minutes, both of a curl height Ci of the initial glass laminate before heating, and a curl height Ch of the glass laminate after heating are 10 mm or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] FIELD OF THE DISCLOSURE The present disclosure relates to glass laminates and methods of making glass laminates. [Background technology]

[0002] Patent Document 1 proposes an optical laminate comprising a glass plate, an adhesive layer, and a film in this order toward one side in the thickness direction, the glass plate having a thickness of less than 40 μm, an average tan δ of the film at −100° C. to −50° C. determined by a dynamic viscoelasticity test in a tensile mode with a frequency of 10 Hz and a heating rate of 2° C. / min is 0.04 or more, and an average tensile storage modulus E′ of the film at −100° C. to −50° C. determined by the dynamic viscoelasticity test is 3 GPa or more and 6 GPa or less. In addition to Patent Document 1, several optical laminates including glass plates have been proposed (Patent Documents 2 to 4, etc.). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Patent Publication No. 2022-83323 [Patent Document 2] Patent Publication No. 2022-83324 [Patent Document 3] Patent Publication No. 2022-83325 [Patent Document 4] Patent Publication No. 2022-83326 Summary of the Invention [Problem to be solved by the invention]

[0004] In order to prevent scratches and ensure a certain degree of ease of handling, thin glass or glass film is used in the form of a glass laminate with a resin film for processing into products. However, even if the glass laminate does not curl at room temperature, it may curl when exposed to high temperatures. When the glass laminate curls, its bending resistance decreases. The curling refers to the phenomenon in which the glass laminate warps and bends. [Means for solving the problem]

[0005] A first aspect of the present disclosure is a glass laminate including a glass film having a first principal surface and a second principal surface, and a resin film bonded to the first principal surface, the product of a long side and a short side being 8000 mm 2 When a measurement sample of the rectangular glass laminate having a long side / short side ratio of 2.5 or less is heated at 100°C and 55% RH for 30 minutes, the initial curl height C of the glass laminate before heating i and the curl height C of the glass laminate after heating h relates to a glass laminate, each of which has a thickness of 10 mm or less.

[0006] A second aspect of the present disclosure relates to a method for manufacturing a glass laminate comprising a glass film having a first main surface and a second main surface, and a resin film adhered to the first main surface, the method comprising: a first step of preparing a precursor film for the resin film; a second step of annealing the precursor film to obtain the resin film; and a third step of adhering the resin film to the first main surface of the glass film to obtain the glass laminate. Effect of the Invention

[0007] This ensures excellent bending resistance of the glass laminate in a high-temperature environment. [Brief description of the drawings]

[0008] [Figure 1] FIG. 1 is a schematic vertical cross-sectional view of a glass laminate according to an embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] A laminate of a glass film such as thin glass and a resin film (hereinafter referred to as a "glass laminate") has a certain degree of flexibility and may be used in applications where it is folded or bent. Even if the glass laminate does not curl at room temperature, it may curl when exposed to high temperatures. This is because the glass film and the resin film expand or shrink to different degrees when heated.

[0010] Conventionally, glass films that have shown excellent results in continuous bending tests at room temperature are considered to have sufficient performance, and are also used in applications where folding and bending are repeated. On the other hand, even in products using glass laminates or glass films that are considered to have sufficient performance, unexpected cracks in the glass film may occur. As a result of investigation into the cause, it was found that even in glass laminates in which the glass film does not crack when repeatedly bent at room temperature, cracks may occur when repeatedly bent at high temperatures (e.g., 80°C). In addition, it was found that in glass laminates that curl significantly when exposed to high temperatures, cracks do not occur in the glass film even when repeatedly bent at room temperature, but cracks may occur when repeatedly bent at high temperatures (e.g., 80°C). In such glass laminates, cracks may become noticeable when repeatedly bent in a high-temperature and high-humidity environment (e.g., an environment of 60°C and 90% RH (relative humidity)). In this specification, room temperature refers to a temperature of 20°C or higher and 35°C or lower.

[0011] In view of the above, (1) a glass laminate according to a first aspect of the present disclosure includes a glass film having a first principal surface and a second principal surface, and a resin film bonded to the first principal surface. 2 When a rectangular glass laminate with a long side / short side ratio of 2.5 or less is heated at 100°C and 55% RH for 30 minutes, the initial curl height C of the glass laminate before heating is i and the curl height C of the glass laminate after heating hThe product of the long side and the short side is the lower limit of 8000 mm. 2 ~10000mm 2 For a measurement sample of about curl height C i and curl height C h If both are 10 mm or less, the curl height C of the glass laminate of a size larger than this i and curl height C h In principle, the product of the long side and the short side is 8000 mm. 2 More than 10000mm 2 It may be the following.

[0012] Thus, the glass laminate of the present disclosure shows a small degree of curling even when heated at 100°C and 55% RH for 30 minutes. A glass laminate showing a small degree of curling after heating suppresses cracking of the glass film even when repeatedly bent in a high-temperature environment. In other words, the glass laminate exhibits excellent bending resistance even in a high-temperature environment.

[0013] Furthermore, when the glass laminate is repeatedly bent in a high-temperature and high-humidity environment, cracking of the glass film usually tends to become more pronounced. However, a glass laminate that shows a small degree of curling after heating can suppress cracking of the glass film and obtain bending resistance even when repeatedly bent in a high-temperature and high-humidity environment.

[0014] As described above, the glass laminate of the present disclosure has excellent bending resistance and high reliability in a high-temperature environment or a high-temperature and high-humidity environment.

[0015] Curl height of glass laminate C i and height C h The product of the long and short sides is 8000 mm 2 or more (e.g. 8000mm 2 More than 10000mm 2The curl height C is determined for a rectangular glass laminate (hereinafter referred to as sample A) with a long side / short side ratio of 2.5 or less before heating. Sample A may be, for example, a sample with a long side / short side ratio of 1.0 (long side = short side). The glass laminate is placed on a flat table with the curl facing up, and the heights of the four corners (the undersides of the four corners) from the top surface of the flat table are measured and averaged. This average value is the curl height C. i or C h is equivalent to.

[0016] Curl Height C h is measured after the glass laminate is heated at 100°C for 30 minutes in a 55% RH environment and cooled to 25°C. i is measured at 25°C in an environment of 55% RH for a glass laminate in its initial state before the glass laminate is subjected to any treatment such as heating.

[0017] (2) In the above (1), the thickness of the glass film may be 50 μm or less. In this case, the glass laminate generally tends to curl when heated, and tends to have low bending resistance in a high-temperature environment and a high-temperature and high-humidity environment. The glass laminate according to the present disclosure has a curl C. h Because of this small size, even when the glass film has a relatively small thickness of 50 μm or less, it can achieve high bending resistance in high temperature and high temperature / high humidity environments.

[0018] The thickness of the glass laminate is also determined as the average value of thicknesses measured at a plurality of locations (for example, five locations) at 25° C. under an environment of 55% RH for the glass laminate in this initial state.

[0019] (3) In the above (1) or (2), the resin film may have a thermal shrinkage or thermal expansion rate of 0.10% or less in the MD and TD directions when heated at 100° C. and 55% RH for 30 minutes. In this case, the curl C of the glass laminate h Therefore, the glass laminate can have even higher bending resistance in a high-temperature environment and a high-temperature and high-humidity environment.

[0020] The thermal shrinkage (or thermal expansion) of the resin film is measured for the resin film after the glass film is peeled off from the glass laminate or for the resin film before being bonded to the glass film (resin film after annealing treatment described later). 2 As described above, a rectangular resin film (hereinafter referred to as sample B) with a long side / short side ratio of 2.5 or less is heated at 100°C for 30 minutes in a 55% RH environment, and the absolute value of the difference between the long side length (mm) before and after heating corresponds to the ratio (%) of the long side length before heating. When sample B is rectangular, it is produced by cutting the resin film so that the MD direction is parallel to the long side and the TD direction is parallel to the short side.

[0021] (4) In any one of the above (1) to (3), when a continuous bending test of a plurality of (e.g., three or more) glass laminates is performed under condition (a) 25°C and 55% RH and condition (b) 80°C and 55% RH, it is preferable that the crack incidence rate, which corresponds to the ratio of the number of samples in which cracks occur in the glass film, is 5% or less under condition (a) and 35% or less under condition (b). In other words, excellent bending resistance in a high-temperature environment of the glass laminate is ensured.

[0022] (5) In any one of the above (1) to (4), when a continuous bending test of a plurality of (e.g., three or more) glass laminates is performed under condition (a) 25°C and 55% RH and condition (c) 60°C and 90% RH, it is preferable that the crack incidence rate, which corresponds to the ratio of the number of samples in which cracks occur in the glass film, is 5% or less under the condition (a) and 35% or less under the condition (c). In other words, excellent bending resistance of the glass laminate in a high-temperature and high-humidity environment is ensured.

[0023] When a continuous bending test of the glass laminate of the present disclosure is performed under the condition (a) for a plurality of samples, 95% or more of the samples show no cracks in the glass film (i.e., the crack occurrence rate is 5% or less). When a continuous bending test of the glass laminate is performed under the condition (b) or (c) similar to the case of the condition (a), 65% or more of the samples show no cracks in the glass film (i.e., the crack occurrence rate is 35% or less). For the continuous bending test, a rectangular glass laminate sample (sample C) with a long side of 152 mm and a short side of 65 mm is used. The long side of sample C may be parallel to the MD direction of the resin film, parallel to the TD direction, or oblique to both.

[0024] (6) In any one of the above (1) to (5), when the long side of the glass laminate to be measured for the curl height is L1, the curl height C h Ratio of to the long side L1: C h / L1 may be 0.1 or less. In this case, the long side L1 and the curl height C h The units are all mm. h When the / L1 ratio is in such a range, higher flex resistance in a high-temperature environment and a high-temperature, high-humidity environment is likely to be obtained.

[0025] (7) The present disclosure also includes a method for producing a glass laminate including a glass film having a first main surface and a second main surface, and a resin film bonded to at least the first main surface. This production method includes a first step of preparing a precursor film of the resin film, a second step of annealing the precursor film to obtain a resin film, and a third step of bonding the resin film to the first main surface of the glass film to obtain a glass laminate. Prior to forming the glass laminate, the resin film constituting the glass laminate is formed by annealing the precursor film, thereby reducing the curl height C when the glass laminate is heated. h In addition, the precursor film is a film in a state before the resin film is annealed.

[0026] (8) In the above (7), in the second step, the annealing treatment may be performed at a temperature of 90° C. or more and 200° C. or less. In this case, the thermal shrinkage rate or thermal expansion rate of the resin film obtained by the annealing treatment is easily reduced. Therefore, the curl height C of the glass laminate is h The annealing treatment may be performed in an environment of, for example, 50% to 60% RH.

[0027] The glass laminate and the method for producing the glass laminate of the present invention, including the above (1) to (8), will be described in more detail below. At least one of the above (1) to (8) may be combined with at least one of the elements described below, provided that there is no technical contradiction.

[0028] When referring to the drawings, the shapes and dimensions of each component in each drawing are not shown to the same scale as in reality. In order to clarify the characteristics of each component, the relative relationship of these dimensions is shown diagrammatically and exaggeratedly.

[0029] [Glass laminate] The glass laminate includes a glass film having a first principal surface and a second principal surface, and a resin film adhered to at least the first principal surface.

[0030] In one aspect of the present disclosure, the product of the long side and the short side is 8000 mm 2 When a rectangular glass laminate with a long side / short side ratio of 2.5 or less is heated at 55% RH and 100°C for 30 minutes, the initial curl height C of sample A before heating is i and curl height C of sample A after heating h In this manner, in the present disclosure, the curl height C of the glass laminate after heating is h This makes it possible to ensure high bending resistance of the glass laminate in a high-temperature environment and a high-temperature and high-humidity environment.

[0031] Initial curl height C i is 10 mm or less, may be 5 mm or less, or may be 1 mm or less. In addition, the initial curl height C i may be 0 mm. Curl height C i is usually the curl height C h Less than.

[0032] Curl Height C h is 10 mm or less, and may be 5 mm or less. h When the thermal shrinkage rate or thermal expansion rate of the resin film included in the glass laminate is so small, the resin film is prevented from expanding or shrinking even when the glass laminate is exposed to a high-temperature environment or a high-temperature and high-humidity environment, so that even when the glass laminate is repeatedly bent under such an environment, cracking of the glass film and peeling between the glass film and the resin film are prevented, and high bending resistance is obtained.

[0033] Curl Height C h and curl height C i The difference between (=C h -C i The difference (C) may be 10 mm or less, 5 mm or less, or 3 mm or less. h -C i When the difference (C) is in such a range, higher bending resistance can be obtained in a high temperature environment or a high temperature and high humidity environment. h -C i ) may be 0 mm.

[0034] The glass laminate of the present disclosure includes a resin film (sometimes referred to as a first resin film) adhered to a first main surface of a glass film. The glass laminate may include a first resin film adhered to the first main surface and a second resin film adhered to the second main surface, as necessary.

[0035] In the glass laminate, the resin film is adhered to a main surface of the glass film via an adhesive layer.

[0036] (glass film) The glass film is generally also referred to as thin glass. It is preferable that the glass film has a uniform thickness.

[0037] The composition of the glass constituting the glass film is not particularly limited. Examples of the glass include soda-lime glass, borate glass, aluminosilicate glass, and quartz glass. The glass may be non-alkali glass or low-alkali glass. The total content of alkali metal components (e.g., Na2O, K2O, Li2O) in the glass may be 15 mass% or less, or 10 mass% or less.

[0038] The thickness of the glass film may be 100 μm or less. The thickness of the glass film may be 50 μm or less, 35 μm or less, or 30 μm or less. When the thickness of the glass film is in such a range, the bending resistance in a high temperature environment and a high temperature and high humidity environment tends to be low. However, in the present disclosure, the curl C h Since the bending resistance is small, even when the thickness of the glass film is within such a range, high bending resistance can be obtained in a high-temperature environment and a high-temperature and high-humidity environment. The thickness of the glass film may be 10 μm or more.

[0039] In this specification, the thickness of each component of the glass laminate is an average value of thicknesses measured at any multiple points (for example, 5 points) of a cross-sectional image, unless otherwise specified. An initial glass laminate is used as a cross-sectional sample for measurement.

[0040] The glass film is manufactured by any suitable method. Typically, the glass film is manufactured by melting a mixture containing ceramics (silica, alumina, etc.) as a main raw material, an antifoaming agent (mirabilite, antimony oxide, etc.), and a reducing agent (carbon, etc.) at a temperature of 1400°C to 1600°C, forming it into a film, and then cooling it. Examples of the glass film forming method include the slot downdraw method, the fusion method, and the float method. The glass film obtained by these methods may be chemically polished with a solvent such as hydrofluoric acid as necessary to further reduce the thickness or improve the smoothness of the surface and edge.

[0041] The surface of the glass film may be subjected to a surface treatment in order to improve adhesion to an adhesive layer in contact with the glass film. The surface treatment is not particularly limited, and examples thereof include a corona treatment, a plasma treatment, and a coupling treatment.

[0042] (Resin film) In the glass laminate, the resin film (first resin film) is adhered to a first main surface of the glass film. When the glass laminate has a second resin film, the second resin film is adhered to a second main surface of the glass film.

[0043] The resin constituting each resin film may be a thermoplastic resin or a thermosetting resin. Examples of thermoplastic resins are polyethersulfone-based resins, polycarbonate-based resins, acrylic-based resins, polyester-based resins, polyolefin-based resins, cycloolefin-based resins, polyimide-based resins, polyamide-based resins, polyimideamide-based resins, polyarylate-based resins, polysulfone-based resins, and polyetherimide-based resins. Examples of polyester-based resins are aromatic polyester-based resins (such as polyalkylene arylate resins). Examples of polyalkylene arylate resins are polyethylene terephthalate (PET) resins, polybutylene terephthalate resins, and polyethylene naphthalate resins. Examples of cycloolefin-based resins are norbornene-based resins. Examples of thermosetting resins are epoxy-based resins, urethane-based resins, and silicone-based resins. However, these resins are merely examples, and the resins constituting the resin films are not limited to these. The resin film may contain one type of resin, or may contain a combination of two or more types of resins. Each resin film may be a single layer or a multilayer. Each layer constituting the multi-layer resin film may contain one type of resin or a combination of two or more types of resin. In consideration of the handling property and strength of the glass laminate, a film made of PET resin is preferable.

[0044] In the present disclosure, the resin film in the glass laminate (or the resin film before being bonded to the glass film) is less likely to shrink or expand when heated, which makes it easier for the glass laminate to curl less when heated and to have high bending resistance in high temperature environments and high temperature and high humidity environments.

[0045] Each resin film may have a thermal shrinkage rate or thermal expansion rate of 0.10% or less when heated at 55% RH and 100°C for 30 minutes. When the thermal shrinkage rate or thermal expansion rate is in such a range, the glass laminate can have even higher bending resistance in high temperature and high humidity environments. The thermal shrinkage rate or thermal expansion rate is measured by the above-mentioned procedure using sample B of the resin film. In a direction parallel to the long side of sample B (MD direction), the thermal shrinkage rate or thermal expansion rate may be 0.10% or less, or may be 0.09% or less. In a direction parallel to the short side of sample B (TD direction), the thermal shrinkage rate or thermal expansion rate may be 0.10% or less, or may be 0.05% or less. The thermal shrinkage rate or thermal expansion rate may be 0.00%.

[0046] The thickness of the resin film may be 10 μm or more, or may be 30 μm or more. When the thickness of the resin film is 50 μm or more, the curl height C h In the present disclosure, even if the thickness of the resin film is in this range, the curl height C h Therefore, high bending resistance in a high temperature environment or a high temperature and high humidity environment can be ensured. The thickness of the resin film may be 100 μm or less, 80 μm or less, or 75 μm or less.

[0047] (Adhesive layer) The glass film and the first resin film are bonded via an adhesive layer. The adhesive layer is formed by applying an adhesive to at least one of the first main surface of the glass film and the main surface of the resin film facing the first main surface of the glass film, stacking the glass film and the resin film so as to sandwich the adhesive, and then pressing and bonding them. More specifically, the adhesive is sandwiched between the glass film and the resin film, and the adhesive is cured while they are pressed in the thickness direction. When the glass laminate has a second resin film, the second resin film may be bonded to the second main surface of the glass film via an adhesive layer, similar to the case of the first resin film.

[0048] In this way, the adhesive layer is formed by curing the coating of the adhesive. Therefore, the adhesive layer does not have substantial fluidity. On the other hand, the adhesive layer composed of the adhesive is non-curable and has fluidity. The storage modulus of the adhesive layer at 25°C may be greater than 10 MPa, 100 MPa or more, and is usually about 1 GPa. In contrast, the storage modulus of the adhesive layer at 25°C is, for example, 10 MPa or less, and is usually 1 MPa or less. In this way, the adhesive layer and the adhesive layer are also distinguished by the storage modulus.

[0049] The storage modulus of the adhesive layer can be measured as the tensile storage modulus in accordance with JIS K 7244-1:1998. Specifically, the adhesive is first formed into a film and cured to produce a cured film having a thickness of about 20 μm. This film is cut to a predetermined size to produce a test piece. The viscoelasticity of this test piece is measured under the following conditions using a dynamic viscoelasticity measuring device (for example, a multi-function dynamic viscoelasticity measuring device "DMS6100" manufactured by Hitachi High-Tech Science Corporation), and the tensile storage modulus at 25° C. is obtained. The measurement may be performed five or more times to obtain an average value.

[0050] Measurement conditions Temperature range: -100℃~+200℃ Heating rate: 2℃ / min Mode: Tensile Sample width: 10mm Chuck distance: 20mm Frequency: 10Hz Distortion amplitude: 10μm Atmosphere: Air (250ml / min) Data acquisition interval: 0.5 min (every 1°C)

[0051] The adhesive is not particularly limited, and any suitable adhesive may be used. Examples of the adhesive include an adhesive containing a resin having a cyclic ether group (such as an epoxy group, a glycidyl group, or an oxetanyl group), an adhesive containing an acrylic resin, and an adhesive containing a silicone resin. The adhesive may be a thermosetting type or a photosetting type (such as an ultraviolet ray curing type).

[0052] The thickness of the adhesive layer may be 0.5 μm or more and 20 μm or less, 1 μm or more and 20 μm or less, or 1 μm or more and 5 μm or less.

[0053] (Crack occurrence rate) When the continuous bending test of the glass laminate is performed under condition (a) 25°C and 55% RH, the cracking rate may be 5% or less, 1% or less, or 0%. The glass laminate of the present disclosure has a low cracking rate even under high temperature and high temperature and high humidity environments. More specifically, when the continuous bending test of the glass laminate is performed under condition (b) 80°C and 55% RH, the cracking rate is preferably 35% or less, more preferably 30% or less or 10% or less. When the continuous bending test is performed under condition (c) 60°C and 90% RH, the cracking rate is preferably 35% or less, more preferably 30% or less or 10% or less. The cracking rate is the ratio (%) of the number of samples in which cracks have occurred to the total number of samples subjected to the continuous bending test. In addition, in the present disclosure, the cracking rate is also low when the continuous bending test of the glass laminate is performed at a low temperature. For example, when the continuous bending test is performed under condition (d) -20°C, the crack occurrence rate may be 30% or less, 10% or less, 5% or less, 1% or less, or 0%. The continuous bending test is performed according to the following procedure.

[0054] (Continuous bending test) A plurality of samples C of the glass laminate (e.g., three samples) are prepared. The shape of the sample C may be, for example, a rectangular shape with a long side of 152 mm and a short side of 65 mm. The sample C is set in a testing machine ("CL09-typeD01-FMC90" manufactured by Yuasa System Devices Co., Ltd.) so that the glass film is on the inside of the bend. In this state, a continuous bending test is performed under the following conditions. The condition of the bent part of the sample C after the test is visually observed, and the number ratio (%) of samples in which cracks are observed is calculated as the peeling rate.

[0055] Environmental conditions: Condition (a) 25°C, 55% RH Condition (b) 80℃, 55%RH Condition (c) 60℃, 90%RH Condition (d) -20℃ Test speed: 60 rpm Bending radius: R1.5mm Number of flexes: 200,000

[0056] (others) When the long side of the glass laminate sample A to be measured for curl height is L1 (unit: mm), the curl height C h Ratio of (unit: mm) to long side L1: C h / L1 may be 0.1 or less, or even 0.05 or less. h When the / L1 ratio is in such a range, higher flex resistance in a high-temperature environment and a high-temperature, high-humidity environment is likely to be obtained.

[0057] The glass laminate may further include other layers as required. For example, a surface coating layer having various functions may be provided on at least a part of the main surface of the glass film as required. Examples of the surface coating layer include an anti-fingerprint coating layer, a hard coating layer, an anti-reflection layer, an anti-glare layer, an anti-fouling layer, an anti-sticking layer, a hue adjusting layer, an antistatic layer, an easy-adhesion layer, a component deposition prevention layer, an impact absorbing layer, and a shatterproof layer. In addition, such a surface coating layer may be provided on the main surface of the resin film opposite to the glass film as required.

[0058] An optical film or a multilayer film including an optical film may be disposed on the main surface of the resin film opposite to the glass film via a pressure-sensitive adhesive layer or adhesive layer. Such a multilayer film may be a multilayer film including an optical film and a base film (such as the above-mentioned resin film), a multilayer film including two or more optical films, or a multilayer film including one or more optical films and a separator. Each film constituting the multilayer film may be directly bonded, or may be bonded via a pressure-sensitive adhesive layer or adhesive layer.

[0059] The optical film is not particularly limited, but may be, for example, a polarizing plate, a retardation plate, or an isotropic film. Examples of materials constituting the optical film include polyvinyl alcohol resins, polyolefin resins, cyclic olefin resins, polycarbonate resins, cellulose resins, polyester resins, polyvinyl alcohol resins, polyamide resins, polyimide resins, polyether resins, polystyrene resins, (meth)acrylic resins, (meth)acrylic urethane resins, polysulfone resins, acetate resins, epoxy resins, and silicone resins. The optical film may be a metal oxide film (metal film, ITO film, etc.), or a laminate film of a metal film and a resin film.

[0060] [Method of manufacturing glass laminate] An example of a method for producing a glass laminate according to the present disclosure will be described below. For components of the glass laminate, the above description of the glass laminate can be referred to.

[0061] The glass laminate is manufactured, for example, by a manufacturing method including a first step of preparing a precursor film for a resin film, a second step of annealing the precursor film to obtain a resin film, and a third step of adhering the resin film to a first main surface of a glass film to obtain a glass laminate.

[0062] (1st step) In the first step, a precursor film is prepared. Examples of the precursor film include films formed from the resin materials exemplified for the resin film. The precursor film may be prepared by film formation, or a commercially available product may be used.

[0063] The size of the precursor film is determined, for example, taking into consideration thermal contraction or thermal expansion due to annealing treatment.

[0064] (2nd process) In the second step, the precursor film is annealed to obtain a resin film. The annealing treatment suppresses the thermal contraction or thermal expansion of the resin film when the glass laminate is exposed to high temperatures, so that the curl height C is reduced compared to when the annealing treatment is not performed. h As a result, high bending resistance of the glass laminate can be ensured in a high-temperature environment and a high-temperature and high-humidity environment.

[0065] In the annealing treatment, the precursor film is heated. The temperature of the annealing treatment may be 90° C. or higher and 200° C. or lower, or 100° C. or higher and 160° C. or lower. When the temperature of the annealing treatment is in such a range, the precursor film is easily brought into a sufficiently thermally shrunk or thermally expanded state, and the curl height C of the glass laminate is reduced. h This is advantageous in reducing

[0066] The annealing time may be 1 minute or more and 60 minutes or less, 5 minutes or more and 40 minutes or less, or 10 minutes or more and 30 minutes or less. When the annealing time is in such a range, the precursor film is easily brought into a sufficiently thermally shrunk or thermally expanded state, and the curl height C of the glass laminate is reduced. h This is advantageous in reducing

[0067] The temperature and time of the annealing treatment are not limited to the above ranges, but may be determined so that the thermal shrinkage or thermal expansion of the resin film when heated at 100° C. for 30 minutes falls within the above ranges.

[0068] The annealing treatment may be carried out in air or in an inert gas atmosphere, such as nitrogen gas, helium gas, or argon gas.

[0069] (3rd step) In the third step, a resin film (first resin film) is bonded to the first main surface of the glass film to obtain a glass laminate. More specifically, an adhesive is applied to at least one of the first main surface of the glass film and the main surface of the resin film opposite to the first main surface, and the glass film and the resin film are pressed together with the adhesive sandwiched between them. At this time, the adhesive is cured to form an adhesive layer. In this manner, a glass laminate in which the glass film and the resin film are bonded together by the adhesive layer is obtained. The adhesive may be cured by heating or by light irradiation depending on the type of adhesive. When the second resin film is bonded to the second main surface of the glass film, a glass laminate is obtained in the same manner as when the first resin film is bonded.

[0070] FIG. 1 is a schematic vertical cross-sectional view illustrating an embodiment of a glass laminate according to the present disclosure. 1 has a glass film 1, a resin film 2, and an adhesive layer 3 interposed therebetween. The glass film 1 has a first principal surface and a second principal surface, and the resin film 2 is adhered to the first principal surface by the adhesive layer 3.

[0071] [Example] The present invention will be specifically described below based on examples and comparative examples, but the present invention is not limited to the following examples.

[0072] Examples 1 to 3 and Comparative Examples 1 to 2 A glass laminate having the layer structure shown in FIG. 3 was produced by the following procedure. (1) Preparation of materials for each layer The following materials were prepared: (precursor film) A biaxially stretched PET film having a thickness of 25 μm (Diafoil T600E25 (registered trademark) manufactured by Mitsubishi Chemical Corporation) was prepared. The PET film was cut so that the long side was parallel to the MD direction and the short side was parallel to the TD direction, to prepare a rectangular precursor film having a long side of 200 mm and a short side of 100 mm.

[0073] (glass film) As the glass film, an ultra-thin glass sheet having a thickness of 30 μm ("G-leaf (registered trademark)" manufactured by Nippon Electric Glass Co., Ltd.) was prepared. The glass film had a rectangular shape in a plan view, and the size was 152 mm long side x 65 mm short side.

[0074] (Adhesive for adhesive layer) An epoxy adhesive was prepared by blending 70 parts by mass of an aliphatic alicyclic epoxy resin (Celloxide 2021P, epoxy equivalent 128 to 133 g / eq., manufactured by Daicel Corporation), 5 parts by mass of a trifunctional aliphatic epoxy resin (EHPE3150, epoxy equivalent 170 to 190 g / eq., manufactured by Daicel Corporation), 19 parts by mass of an oxetane resin (Aron Oxetane (registered trademark), manufactured by Toa Gosei Co., Ltd.), 4 parts by mass of a silane coupling agent (KBM-403, 3-glycidoxypropyltrimethoxysilane, manufactured by Shin-Etsu Chemical Co., Ltd.), and 2 parts by mass of a photoacid generator (CPI101A, triarylsulfonium salt, manufactured by San-Apro Ltd.).

[0075] (2) Annealing The precursor film prepared in (1) above was annealed by heating at a temperature shown in Table 1, at 50% to 60% RH, for a time shown in Table 1 to obtain a resin film (PET film). In Comparative Example 1, the annealing treatment was not performed, and the precursor film was used as the resin film.

[0076] (3) Formation of glass laminate An adhesive was applied to both one of the main surfaces of the resin film obtained in (2) above and the first main surface of the glass film to form a coating film, and the two were then bonded together. The obtained laminate was pressed in the thickness direction while being irradiated with UV light to harden the adhesive, forming an adhesive layer. In this way, a glass laminate was formed.

[0077] (4) Evaluation The resin film or glass laminate was used to carry out the following evaluations.

[0078] (4-1) Thermal shrinkage rate of resin film The resin film was cut to a size of 100 mm x 100 mm to prepare Sample B. The initial dimensions of Sample B were measured using a Mitutoyo image measuring instrument "QVA606-PRO_AE10." Next, Sample B was heated at 55% RH and 100°C for 30 minutes using the procedure described above, and the dimensions were measured again. The thermal shrinkage rate (%) was calculated using the following formula. The dimensions were measured in both the MD and TD directions.

[0079] Heat shrinkage rate (%) = {(initial dimension - dimension after heating) / (initial dimension)} x 100

[0080] (4-2) Curl height C i and C h A glass laminate having a long side (MD direction) of 152 mm and a short side (TD direction) of 65 mm was prepared as sample A. Sample A was used to measure the curl height C i and C h asked for.

[0081] (4-3) Continuous bending test A glass laminate having a size of 152 mm long side (MD) × 65 mm short side (TD) was produced as Sample C. Using Sample C, a continuous bending test was performed under each of the conditions (a) to (d) according to the procedure described above, and the peeling rate was determined.

[0082] The results of the Examples and Comparative Examples are shown in Table 1. In Table 1, A1 to A3 correspond to Examples 1 to 3, and B1 and B2 correspond to Comparative Examples 1 and 2.

[0083] [Table 1]

[0084] As shown in Table 1, the curl height C h In the Examples where the cracking rate is 10 mm or less and the Comparative Examples where the cracking rate is over 10 mm, the cracking rate in the continuous bending test is low under condition (a) or condition (d), being 0% in both cases. However, under a high temperature environment (condition (b)) or a high temperature and high humidity environment (condition (c)), the cracking rate in the continuous bending test is significantly higher in the Comparative Examples. In contrast, the Examples have a low cracking rate and excellent bending resistance under both a high temperature environment and a high temperature and high humidity environment. [Industrial Applicability]

[0085] The glass laminate of the present disclosure has high reliability due to its excellent resistance to bending under high temperature environments. Therefore, the glass laminate is suitable for applications requiring excellent appearance and high bending properties of a glass film (such as applications for cover windows of foldable devices or flexible devices). However, the applications of the glass laminate are not limited to these. [Explanation of symbols]

[0086] 1 Glass film 2. Resin film 3 Adhesive layer 11 Glass laminate

Claims

1. A glass laminate comprising a glass film having a first main surface and a second main surface, and a resin film adhered to the first main surface, The product of the long and short sides is 8000 mm 2 The glass laminate as described above, wherein when a measurement sample of the rectangular glass laminate having a long side / short side ratio of 2.5 or less is heated at 100°C and 55% RH for 30 minutes, an initial curl height Ci of the glass laminate before heating and a curl height Ch of the glass laminate after heating are both 10 mm or less.

2. The glass laminate according to claim 1 , wherein the glass film has a thickness of 50 μm or less.

3. 3. The glass laminate according to claim 1, wherein the resin film has a thermal shrinkage or thermal expansion coefficient of 0.10% or less when heated at 100° C. and 55% RH for 30 minutes.

4. When a continuous bending test of the glass laminate is performed under condition (a) of 25° C. and 55% RH and condition (b) of 80° C. and 55% RH, a crack occurrence rate corresponding to the number ratio of samples in which cracks occur in the glass film is: In the condition (a), it is 5% or less, The glass laminate according to claim 1 or 2, wherein the ratio under condition (b) is 35% or less.

5. When a continuous bending test of the glass laminate is performed under condition (a) of 25° C. and 55% RH and condition (c) of 60° C. and 90% RH, a crack occurrence rate corresponding to the number ratio of samples in which cracks occur in the glass film is: In the condition (a), it is 5% or less, The glass laminate according to claim 1 or 2, wherein the thickness under condition (c) is 35% or less.

6. When the long side is L1, the curl height C h to the long side L1: C h / L1 is 0.1 or less, The long side L1 and the curl height C h The glass laminate according to claim 1 or 2, wherein the units of are all mm.

7. A method for producing a glass laminate including a glass film having a first principal surface and a second principal surface, and a resin film bonded to the first principal surface, comprising: A first step of preparing a precursor film of the resin film; A second step of annealing the precursor film to obtain the resin film; and a third step of bonding the resin film to the first main surface of the glass film to obtain the glass laminate.

8. The method for producing a glass laminate according to claim 7, wherein in the second step, the annealing treatment is carried out at a temperature of 90°C or higher and 200°C or lower.

Citation Information

Patent Citations

  • Optical laminate and optical laminate having adhesive layer

    JP2022083323A

  • Optical laminate

    JP2022083324A

  • Optical laminate

    JP2022083325A

  • Optical laminate

    JP2022083326A